The challenge of reducing non-revenue water (NRW) in developing countries : - Kingdom, Bill (World Bank, 2006)
In this report, a number of case studies, taken from some of the largest and most recent performance-based non- revenue water (NRW) contracts, are studied and discussed in terms of their technical and financial performance. Lessons learned from the case studies are analyzed, showing the potential benefits of NRW performance-based service contracting with the private sector. Although performance-based service contracting for NRW reduction is a new approach and none of the contracts reviewed could be described as “best-practice”, these early experiences hold useful lessons for water practitioners. The limited evidence available suggests that performance-based service contracting can be very efficient in reducing NRW levels. It is based on a more efficient contractual framework than the traditional technical assistance approach, with the private sector being accountable for results through financial incentives, while having at the same time the necessary flexibility and resources to carry out the many activities needed to make a meaningful impact on NRW levels